A new species of Cernotina (Trichoptera, Polycentropodidae) from the Atlantic Forest, Rio de Janeiro State, southeastern Brazil - Dumas,Leandro Lourenço (2011)
A new species of Cernotina (Trichoptera, Polycentropodidae) from the Atlantic Forest, Rio de Janeiro State, southeastern Brazil. Cernotina Ross, 1938, with 64 extant species, is a New World genus of caddisflies. In Brazil, there are 31 described species of which 28 are recorded from the Amazon basin. Cernotina puri sp. nov. is described and figured based on specimens collected in the Atlantic Forest, Rio de Janeiro State, Brazil. The new species can be distinguished by the shape of the intermediate appendages and tergum X. The immature stages of C. puri are unknown.